2020
DOI: 10.1007/s12649-020-01069-3
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Several Vegetable Origin Household Waste Extracts Against Wood-Decaying Fungi In Vitro

Abstract: The aim of this paper is to identify if vegetable origin household wastes (VHWs) can be used in wood preservative formulations. Method An antifungal activity test of the VHW hot water extracts against wood-decaying fungi in vitro was performed. Results Out of the 17 studied VHW extracts 14 showed some antifungal activity against at least one fungi. Extracts from banana, tangerine and watermelon peels and discarded onion peels inhibited fungal growth the most. Conclusions The results demonstrate that VHWs are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…BPW has antibacterial activities against Proteus vulgaris and Klebsiella pneumoniae [ 87 ]. BPW extracts have used to inhibit the growth of Gloeophyllum trabeum , Rhodonia placenta and Trametes versicolor [ 35 ]. The study by Prakash et al [ 259 ] has demonstrated that BPW extracts are an effective inhibitor of A. niger .…”
Section: Tpw Ppw and Bpw Valorisation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BPW has antibacterial activities against Proteus vulgaris and Klebsiella pneumoniae [ 87 ]. BPW extracts have used to inhibit the growth of Gloeophyllum trabeum , Rhodonia placenta and Trametes versicolor [ 35 ]. The study by Prakash et al [ 259 ] has demonstrated that BPW extracts are an effective inhibitor of A. niger .…”
Section: Tpw Ppw and Bpw Valorisation Methodsmentioning
confidence: 99%
“…Moreover, some bioactive compounds from TPW have been reported to form protective enzymes in the liver and block the deterioration of genetic material in cells [ 74 ]. TPW extracts have a capacity to inhibit the growth of Gloeophyllum trabeum, Rhodonia placenta and Trametes versicolor [ 35 ].
Fig.
…”
Section: Tpw Ppw and Bpw Valorisation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts that exhibit antifungal activity, such as the extracts of mimosa bark (Acacia mollissima) and quebracho (Schinopsis lorentzii) [33], as well as the essential oils of P. graveolens and their fractions [34], and the mistletoe leaves and extracts of lichen [35], extracts from the heartwood of Teak (Tectona grandis) [36], extracts of propolis [37] and extracts from the peel of fruits and vegetables [38] have great potential with preservatives for wood. As can be seen, research with natural extracts has been extensive and has proven to be effective in resisting biodeterioration, but its leaching of wood into the environment remains a challenge to be overcome.…”
Section: Tablementioning
confidence: 99%
“…Finding sustainable and abundant feedstocks for these chemicals is still under investigation. Although the valorisation of household waste has been studied (Shiny et al 2017, Lajnef et al 2018, Barbero-López 2020, industrial residues, due to their high availability, low price and the current lack of profitable refining routes, should be especially considered. Companies from different countries or regions should consider different feedstocks, considering the availability, environmental conditions and the tolerance of fungi to the chemicals.…”
Section: Synthetic Chemicals and Bio-based Preservation Compoundsmentioning
confidence: 99%